Implementasi Supervisi Manajerial dalam Meningkatkan Mutu Pendidikan Paud Almanshuriyah Kota Sukabumi - Neneng Neneng; Siti Qomariyah; Najrul Jimatul Rizki; Rima Erviana (Institut Nalanda, 2024)
The This research aims to analyze the implementation of managerial supervision in improving the quality of education in Early Childhood Education (PAUD). The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews and documentation. The research subjects included school principals, teachers and administrative staff at Almanshuriyah Paud. The research results show that effective managerial supervision can improve the quality of education in PAUD through several aspects, including: increasing teacher competency, better curriculum implementation, management of facilities and infrastructure optimal, as well as the development of a conducive learning environment. Managerial supervision carried out routinely and in a structured manner is able to identify educational deficiencies and needs accurately, as well as provide concrete and applicable solutions. In addition, this research found that active participation from all stakeholders, including students' parents, is very important in supporting the success of managerial supervision. Thus, managerial supervision not only functions as a monitoring tool, but also as a mechanism for developing and improving the quality of education on an ongoing basis. The implications of this research indicate that improving the quality of education in PAUD requires a strong commitment from management to implement effective and sustainable supervision. Research recommendations include the need for training and professional development for school principals and teachers, as well as strengthening collaboration between schools and communities, managerial supervision not only functions as a monitoring tool, but also as a mechanism for developing and improving the quality of education on an ongoing basis.output.